Review: Rotor Balancing - W.C. Foiles; P. E. Allaire; E. J. Gunter (Shock and Vibration)
This article reviews the literature concerning the balancing of rotors including the origins of various balancing techniques including ones that use influence coefficient, modal, unified, no phase, and no amplitude methods to balance. This survey covers the computational algorithms as well as the physical concepts involved in balancing rotating equipment.